Regional Strategic Analysis and Knowledge Support System (Re-SAKSS) - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: The Regional Strategic Analysis and Knowledge Support System (ReSAKSS) is an Africa-wide network established to provide readily available analysis, data, and tools of the highest quality to promote evidence-based decision-making, improve awareness of the role of agriculture for development in Africa, fill knowledge gaps, promote dialogue, and facilitate the benchmarking and review processes associated with the CAADP agenda.